A UPLC-MS/MS method for simultaneous determination of tiamulin and its metabolites in Crucian carp (Carassius carassius): an in vivo metabolism and tissue distribution study - Wang, Qianfeng; Fan, Zhengli; Zhang, Xiaojun; Yang, Qiyu; Zhong, Yaqian; Liu, Wenjing (Frontiers in Marine Science, 2024)
Tiamulin (TML) has been studied and analyzed in pigs, cattle, chickens, ducks, and other domestic animals, however, its metabolic state in fish has not been well explored. This study investigated TML metabolism in Crucian carp (Carassius carassius). After intraperitoneal injection of TML into Crucian carp, ultra-high performance liquid chromatography with quadrupole and time-of-flight mass spectrometry (UPLC/Q-TOF MS) analysis, was conducted to identify TML metabolites. The UPLC/Q-TOF MS analysis and the relative molecular mass of the metabolites obtained from related literature identified five metabolites in Crucian carp. These metabolites were M1 (510.2908, C28H48NO5S+), M2 (510.2908, C28H48NO5S+), M3 (466.2750, C26H44NO4S+), M4 (482.2663, C26H44NO5S+), and M5 (482.2663, C26H44NO5S+). The enrichment and metabolism of TML and its metabolites in Crucian carp were investigated using the drug bath method combined with ultra-high performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). TML exhibited an overall trend of an initial increase followed by a decrease. Moreover, the drug enrichment rate was fast and reached saturation after two days. The bioconcentration factor of TML in Crucian carp was 3.01. However, the drug had a slow elimination rate, with its complete metabolism occurring after 20 days.